Researching the Impact of the Economic Crisis on Student Life in Greece - Kouroutsidou, Maria; Raptis, Nikolaos; Karampelas, Konstantinos (International Journal of Learning, Teaching and Educational Research, 2020)
The present work explores the views of students in Greek Universities who have been impacted by the economic crisis in Greece since 2009. In the theoretical part, the economic crisis is considered a violent change that tends to be incorporated permanently into socio-economic life, affecting public expenditure in tertiary education as well as family income and expenditure. These developments harm university studies, student life, and expectations of graduates for their future. The theoretical part ends with the formulation of three research axes about the extent to which the economic crisis affects (a) the socio-economic environment and family spending, (b) students’ life at the university, and (c) students’ perception of their future. In the empirical part, a series of questions along these axes are investigated quantitatively, through descriptive statistics using a questionnaire specially constructed for this research, which addressed to students. The sample comprised 300 university students. Their views seem to primarily support the hypothesis of the negative impacts of the economic crisis on families, studies, and expectations. The study ends with suggestions for further research. https://doi.org/10.26803/ijlter.19.7.8